Awareness and practice on household solid waste management among residents in rural areas at Alor Pongsu, Kerian district - Mohamad, Nor Hamimi (2023)
As we know, improper household solid waste management causes various diseases to humans and causes a bad impact on the environment. This often happens in rural areas, where they do not have an effective waste management system like urban areas, which causes most rural residents to still practice traditional ways to manage their household solid waste, such as burning in the backyard. Descriptive correlational study design was used as the method for this study. The data was collected in December 2022. The number of respondents was needed for this study is 142 and has been chosen by simple random sampling. The data were collected by face-to-face interview by using the questionnaire. After finishing collecting the data, the data were analyzed by using SPSS Version 28.00. Results from this study show that residents in rural areas at Alor Pongsu, Kerian District toward awareness and practice on managing solid waste at home were at moderate levels. Mean awareness on household solid waste was 6.965 (SD = 3.209) and the mean for practice level was 2.429 (SD = 0.593). For relationship between socio demographic with awareness level, it has been show that age (p <0.001), marital status (p<0.001), education level (p<0.001), problem in household solid waste management (p = 0.038) and training on household solid waste management (p < 0.001) were significantly correlated with awareness level. For the relationship between socio demographic and practice level, it has been found that training on household solid waste management (p = 0.003) was significantly correlated with practice level. Conclusion, this study highlights the importance of household solid waste management awareness and practice among rural residents towards good sustainable management of household solid waste practice.